The king of spices: on pepper's pungent pleasure - Spence, C (Elsevier, 2024)
Pepper (Piper nigrum Linn.), and its key pungent constituent piperine (an alkaloid), has long been one of the world's most popular spices. Interestingly, it is one of the only culinary spices (along with the mineral salt) that is to be found on/at the dining table around the world. Known as the ‘king of spices’, pepper possesses a number of beneficial anti-microbial and anti-carcinogenic properties, as well as a gustatory pungency that chefs and consumers in many countries have long found highly-desirable. Given that pepper is already found on many dining tables around the world, together with the fact that it delivers a pungent boost to the flavour of food (without any of the obvious negative health consequences, or adverse public perception, of other flavour enhancers such as monosodium glutamate or kokumi), it would appear to be ideally positioned as a healthy flavour enhancer, one that also allows the consumer to personalize their tasting experience. That said, the results of research where pepper has been added directly to a recipe, rather than the consumer adding it themselves, have not always given rise to a positive result, suggesting that the ability to add it oneself (i.e., to taste) may play an important part in the consumer's overall enjoyment of the flavour of this spice.